(untitled) (Scientific Journal of Actuarial Finance and Accounting, 2025)
This paper explores the advantages and disadvantages of small businesses compared to large corporations. It highlights key factors such as flexibility, innovation, customer relationships, resource availability, and market reach. While small businesses offer agility and personalized services, large corporations’ benefit from vast resources and global influence. Understanding these differences helps entrepreneurs and policymakers make informed decisions about business development strategies.